Research on the Innovative Path of Community Group-Buying Model for Agricultural Products under the Background of Digital Transformation - Xiangcui Li; Wenji Li (Journal of Innovation and Entrepreneurship, 2025)
Against the backdrop of the vigorous development of the digital economy and the in-depth promotion of the rural revitalization strategy, the digital transformation of the agricultural product circulation system has become a key path to addressing the “issues related to agriculture, rural areas, and farmers.”Based on the theories of business model innovation and community e-commerce, this paper systematically explores the innovative path of the community group-buying model of agricultural products in the context of digital transformation, using methods such as literature analysis, case studies, and comparative analysis. The research findings are as follows: (1) The community group-buying model of agricultural products effectively solves problems such as information asymmetry, lengthy supply chains, and high loss rates in traditional agricultural product circulation through the core mechanism of “direct supply from the production area + community operation + pre-sale centralized procurement”; (2) The in-depth application of digital technology has given rise to an innovative path combining “intelligent supply chain + social marketing + content e-commerce,” achieving a shift from pure product transactions to value co-creation; (3) This model demonstrates significant advantages in reducing circulation costs, enhancing farmers’ income, and ensuring product quality, but still faces challenges such as supply chain management, standardization of quality control, and user operation. This study provides theoretical support and practical guidance for promoting the construction of a digital circulation system for agricultural products.